The Role of Endogenous Eicosapentaenoic Acid and Docosahexaenoic Acid-Derived Resolvins in Systemic Sclerosis - Avanoǧlu Güler, Aslıhan; Rossi, Francesca Wanda; Bellando-Randone, Silvia; Prevete, Nella; Tufan, Abdurrahman; Manetti, Mirko; de Paulis, Amato; Matucci-Cerinic, Marco (Frontiers in Immunology, 2020)
Resolvins, the member of specialized pro-resolving mediators, are produced from omega-3 polyunsaturated fatty acids as a response to an acute inflammatory process in that termination and resolution of inflammation. In the acute inflammation, these lipid mediators limit polymorphonuclear cells infiltration, proinflammatory cytokine production; promote efferocytosis, and regulate several cell types being important roles in innate and adaptive immunity. Any dysregulation or defect of the resolution phase result in prolonged, persistent inflammation and eventually fibrosis. Resolvins are implicated in the development of various chronic autoimmune diseases. Systemic sclerosis (SSc) is a very complicated, chronic autoimmune disorder proceeding with vasculopathy, inflammation, and fibrosis. Dysregulation of innate and adaptive immunity is another important contributing factor in the pathogenesis of SSc. In this review, we will focus on the different roles of this new family of lipid mediators, characterized by the ability to prevent the spread of inflammation and its chronicity in various ways and how they can control the development of fibrotic diseases like SSc.